Coupling to continuum effects in the 6, 7Li +64Zn reactions at energies around the Coulomb barrier. (March 2015) - Fernández-García, J P; Zadro, M; Di Pietro, A; Figuera, P; Fisichella, M; Lattuada, M; Moro, A M; Torresi, D
Abstract: The elastic scattering angular distributions for the weakly bound nuclei 6 Li and 7 Li on 64 Zn were measured in a wide angular range at energies around the Coulomb barrier. In addition, the excitation functions of quasi-elastic scattering at backward angles were measured and the corresponding barrier distributions were derived. The experimental data were analysed within the continuum-discretized-coupled-channel method. In this contribution, we will present a detailed study concerning the effects of the break-up channels in the 6, 7 Li + 64 Zn reactions.